Understanding the human knee and its relationship to total knee replacement - Vaienti, Enrico; Scita, Giacomo; Ceccarelli, Francesco; Pogliacomi, Francesco (Acta Biomedica Atenei Parmensis, 2017)
The knee is the intermediate joint of the lower limb and it allows the movement between the femur, tibia and patella. Under normal conditions there is a normal distribution of the load forces on these three articular components in both the static load and during ambulation. The understanding of anatomy and knee biomechanics is important for the gait analysis, the diagnosis of joint diseases and the design and development of prosthetic implants. In the last decades comprehension of knee physiology and kinematics has led to the introduction of a wide range of enhanced prosthetic implant designs for a variety of indications. There are a number of types of total knee arthroplasty implant designs, which are intended to offer the surgeon options for individual patients. The various choices imply that each specific problem has a corresponding implant that provides a reliable solution. However, until the current date, it has not been possible to produce a prosthetic design fully restoring the complex kinematics of the normal knee joint.